Expanded text score determination method and device, equipment and storage medium - LEI YANQIANG; LEE HYUN; BAN ZHIHUA (2024)
The invention discloses a score determination method and device for an expanded text, equipment and a storage medium. The method comprises the steps of obtaining a to-be-expanded statement and first score information of the to-be-expanded statement; determining a first sentence accuracy comprehensive score and a first word accuracy comprehensive score according to the first score information and the score gear information of the to-be-expanded statement; expanding the to-be-expanded statement to generate at least one target statement text; for each target statement text, determining at least one second word accuracy score corresponding to the target statement text, and determining a second sentence accuracy comprehensive score of the target statement text according to each second word accuracy score, each first word accuracy comprehensive score and the first sentence accuracy comprehensive score, the problem that the score of the expanded text cannot be automatically determined is solved, manual scoring is no